KELOMPOK WIRA USAHA IBU ‘MANDIRI’ DI DESA PARIA, WAJO – SULAWESI SELATAN - -, Feizarina (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Paria village is one of the villages of the District Majauleng, Wajo, SouthSulawesi. The majority of the population is farmer and the Civil Service, has a page /home gardens that grow coconut trees. These conditions will certainly provide manyopportunities coconut production of every household in the region. If at any householdstore coconuts falling on their inventory in the warehouse, then made the traditionalcooking oil on the end result will produce blendo. The utilization of this limited blendostill need to be handled to be made into confectionary are more varied andeconomically better than any housewife group in this region.Standard manufacture of one kilogram of cooking oil traditional / kelntik and 500grams blendo produced from coconuts seven medium-size (1: 7). For the re sep makeschips